Characterizing air source heat pump market segments: A Canadian case study - Pardy, Aaron; Rhodes, Ekaterina; Jaccard, Mark (Frontiers in Sustainability, 2022)
Electric air source heat pumps (ASHPs) appear to be a key technology for decarbonizing space heating in existing residential buildings, yet their current market share in much of North America remains low. To explore how the potential future ASHP market may differ from the present one, we use a subset of data from the Canadian Home Heating Survey (n=461) to provide a comprehensive characterization of three market segments of British Columbian homeowners: Pioneers (heat pump owners), Potential Early Mainstream buyers (homeowners currently willing to purchase an ASHP), and Late Mainstream buyers (homeowners currently unwilling to purchase an ASHP). We assess variable associations with market segments according to the Attitude-Behavior-Context theory, which posits that pro-environmental behavior is shaped by attitudinal, contextual, and socio-demographic factors. We also compare how market segmentation changes before and after respondents receive technical information on different home heating systems. Relative to Pioneers and the Potential Early Mainstream (PEM), we find that the Late Mainstream (LM) are generally lower income, lower educated, less environmentally- and technology-oriented in their lifestyles, less open to change, less familiar with heat pumps and home energy efficiency, more negative in their perceptions about heat pumps, and less aware and supportive of policies aimed at reducing residential emissions. We also find that after respondents read technical information about home heating systems, approximately 10% of heat pump non-owners shift from the LM to the PEM; however, within the PEM, there is little growth in high willingness to adopt.